High-throughput toxicity screening of novel azepanium and 3-methylpiperidinium ionic liquids. Issue 39 (16th June 2020) - Tether, Angela L.; Laverty, Garry; Puga, Alberto V.; Seddon, Kenneth R.; Gilmore, Brendan F.; Kelly, Stephen A.
Abstract : Ionic liquids have been employed as potentially environmentally friendly replacements for organic solvents, but have also been studied for their use in bioelectrochemical applications, such as bioenergy production, or in industrial biocatalysis. Abstract : Ionic liquids (ILs) have been employed as potentially environmentally friendly replacements for harmful organic solvents, but have also been studied for their use in bioelectrochemical applications, such as in microbial electrochemistry for bioenergy production, or in industrial biocatalysis. For these processes, low microbial toxicity is important and there is a growing need for microbial toxicology studies for novel ILs. In this study, we report initial toxicity data for novel ILs, based on azepanium and 3-methylpiperidinium cations. Agar disc diffusion assays are used, along with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determinations, to obtain rapid and inexpensive initial toxicity data for these novel ILs against Escherichia coli and Staphylococcus epidermidis . Many of the novel ILs characterised possess low microbial toxicity relative to well-studied ILs, highlighting their potential for further study in applications where this is a desirable property.